Examining the Impact of Board Committees on the Relationship between Corporate Investment and Financial Performance - Sajwani, Burair A.; Al-Shboul, Mohammad (International Journal of Energy Economics and Policy, 2026)
This study examines the role of corporate governance, specifically its representation on board committees, on the relationship between corporate investments and financial performance. We use quarterly data from 441 publicly traded non-financial US companies between 2010 and 2023. By employing the GMM methodology, the results show that corporate investment is adversely associated with financial performance, supporting the hypothesis of an underinvestment problem. Our findings also suggest that corporate governance, as represented by board committees, the supervisory and executive authorities—plays a pivotal role in mitigating the negative impact of corporate investments on firm’s financial performance. Furthermore, we note that the relationship between corporate governance and investments affects high-performing and low-performing companies differently, confirming the existence of asymmetry effect within the nexus between corporate governance and corporate investment across low and high-performing firms. The originality of this research lies in its comprehensive analysis of the role of strategic board committees—such as the Sustainability and Corporate Social Responsibility Committee, the Audit Committee, the Corporate Governance Committee, the Nominations Committee, and the Compensation Committee—in terms of the relationship between investment decisions and company performance, a topic rarely examined in the literature. The study's findings also offer practical implications for shareholders and decision-makers by strengthening oversight mechanisms and improving investment decisions.